Pathways and challenges towards a complete characterization of microgels - Frank Scheffold (Nature Portfolio, 2020)
Despite their widespread use, many fundamental questions about the internal structure of microgels are still open. Here the authors describe several pathways toward a complete understanding of microgel colloids based on recent experimental advances in nanoscale characterization.